Students’ Perception on the Use of Visual Media to Increase Their Motivation and Creativity in Writing Narrative Text - Putri, Dini Puspita; Safitri, Dian (Universitas Negeri Padang, 2024)
The aim of this research is to reveal students' perception on the use of visual media to increase their motivation and creativity in writing narrative text. This research uses descriptive research with a quantitative approach. The population of this research is class VIII at SMP Negeri 22 Padang with a sample of class VIIID-VIIIG. This research used a purposive sampling technique because the classes applied for learning using visual media were only class VIIID-VIIIG. The instrument used to collect data was a questionnaire with 23 close-ended statements using 4 Likert scales, including strongly agree, agree, disagree, and strongly disagree. The results of this research show that students are interested in learning using visual media. This can be seen from the research tabulation results which show a total mean of motivation indicators of 3.26 (Very Positive) and creativity indicators of 3.34 (Very Positive). The total of the two indicators is 3.30, which means Very Positive. Even though there were differences of opinion on students' responses. Some students gave disagreeing and strongly disagree responses to the statements in the questionnaire because some factors. So, suggestions for further researcher are investigating what factors contribute to the weaknesses of using visual media in teaching English for EFL students.The aim of this research is to reveal students' perception on the use of visual media to increase their motivation and creativity in writing narrative text. This research uses descriptive research with a quantitative approach. The population of this research is class VIII at SMP Negeri 22 Padang with a sample of class VIIID-VIIIG. This research used a purposive sampling technique because the classes applied for learning using visual media were only class VIIID-VIIIG. The instrument used to collect data was a questionnaire with 23 close-ended statements using 4 Likert scales, including strongly agree, agree, disagree, and strongly disagree. The results of this research show that students are interested in learning using visual media. This can be seen from the research tabulation results which show a total mean of motivation indicators of 3.26 (Very Positive) and creativity indicators of 3.34 (Very Positive). The total of the two indicators is 3.30, which means Very Positive. Even though there were differences of opinion on students' responses. Some students gave disagreeing and strongly disagree responses to the statements in the questionnaire because some factors. So, suggestions for further researcher are investigating what factors contribute to the weaknesses of using visual media in teaching English for EFL students.